Thermostability and Protein Studies of Newcastle Disease Virus - Hassan, Zuridah (1995)
The heat stability of four strains of Newcastle disease virus (NDV) belonging to three different pathotypes were studied. The strains were the lentogenic V4 and its heat stable variant V4-UPM, the mesogenic S strain and the velogenic strain AF2240. Analyses of their haemagglutination and neuraminidase activities (which are the functions of the HN protein) and the hemolytic activities at various temperatures showed that strains AF2240, V4 and V4 -UPM were heat stable compared to strain S. There were no differences observed in the mobilities of the various NDV proteins on sodium dodecyl sulphate-polyacrylamide gel electrophoretic (SDS-PAGE) studies. However, analysis of the various peptides with Staphylococcus aureus protease showed that the digested HN proteins of strain V4-UPM was different from the strains V4, AF2240 and S. The peptide analysis was repeated using Pseudomonas fragi Endoproteinase Asp-N and Lysobacter enzymogenes Lys-C and found to be similar except in strain V4-UPM. These proteins were further analysed by the two dimensional polyacrylamide gel electrophoresis (2DPAGE). The gels were then Western blotted and protein spots were identified using HN,NP and Fi Mabs and then analysed by the UVP GDS Gel Documentation System (United Kingdom). It was observed that in the heat stable V4 strain the isoelectric point (pI) of the HN protein was in the acidic region, strains V4-UPM and AF2240 in the neutral/weak basic regions and in the thermolabile strain s, the HN protein was shifted to the basic end of the isoelectric focussing run. The pI changes in the NP protein was seen in strain S only. The F protein was at the basic region for all strain except strain V4-UPM. In strain S it was seen that the HN, NP and F proteins were in the basic region and this basic pI could be responsible for the different biological characteristics seen in the thermostable strains compared to the thermosensitive strain.